Space charge limited current in an ideal GaN heterojunction field effect transistor with no back-barrier. (July 2021) - Tripathi, Durgesh C.; Ritter, D.
Abstract: If neither traps nor a back-barrier is included in an ideal GaN heterojunction field-effect transistor, its performance is severely degraded by space charge limited current through the buffer layer. This effect is analyzed here by simulation, showing that it results in significant current leakage in the off state not only in short channel devices but also in long channel devices. The output resistance at saturation is also set primarily by space charge limited current through the buffer.